Laparoscopic bladder diverticulectomy in a child with situs inversus totalis: A case report and literature review - Chen, Jitao; Liu, Fei; Tian, Jie; Xiang, Mingfeng (Frontiers in Surgery, 2022)
Situs inversus totalis (SIT) is a rare internal laterality disorder characterized by the mirror arrangement of organs. Multiple gene mutations and maternal environmental factors are thought to cause this variation. It is usually challenging to perform laparoscopic surgery in these cases. Bladder diverticulum is uncommon in children, with an incidence of 1.7%. We report a 14-year-old male patient who was admitted to our department because of lower abdominal pain and frequent urination. A series of examinations confirmed the rare combination of giant bladder diverticulum and SIT. After extensive preoperative discussion, we performed laparoscopic bladder diverticulectomy. The operation was successful. To the best of our knowledge, this is the first report of successful laparoscopic bladder surgery on a case of SIT. This article summarizes the key technical points and the difficulties of performing this kind of operation. In addition, during the process of reviewing the literature, we found that SIT often coexists with some high-risk factors for bladder diverticulum in some rare syndromes. It is helpful to further understand and provide experience in the diagnosis and treatment of the rare combination of bladder diverticulum and SIT in children.